Retrieving water productivity parameters by using Landsat images in the Nilo Coelho irrigation scheme, Brazil - Teixeira, Antonio H. de C.; Lopes, Helio L.; Hernandez, Fernando B. T. [UNESP]; Sherer-Warren, Morris; Andrade, Ricardo G.; Neale, Christopher M. U.; Neale, CMU; Maltese, A. (Spie-int Soc Optical Engineering, 2013)
The Nilo Coelho irrigation scheme, located in the semi-arid region of Brazil, is highlighted as an important agricultural irrigated perimeter. Considering the scenario of this fast land use change, the development and application of suitable tools to quantify the trends of the water productivity parameters on a large scale is important. To analyse the effects of land use change within this perimeter, the large-scale values of biomass production (BIO) and actual evapotranspiration (ET) were quantified from 1992 to 2011, under the naturally driest conditions along the year. Monteith's radiation model was applied for estimating the absorbed photosynthetically active radiation (APAR), while the SAFER (Simple Algorithm For Evapotranspiration Retrieving) algorithm was used to retrieve ET. The highest incremental BIO values happened during the years of 1999 and 2005, as a result of the increased agricultural area under production inside the perimeter, when the average differences between irrigated crops and natural vegetation were more than 70 kg ha(-1) d(-1). Comparing the average ET rates of 1992 (1.6 mm d(-1)) with those for 2011 (3.1 mm d(-1)), it was verified that the extra water consumption doubled because of the increments of irrigated areas along the years. More uniformity along the years on both water productivity parameters occurred for natural vegetation, evidenced by the lower values of standard deviation when comparing to irrigated crops. The heterogeneity of ET values under irrigation conditions are due to the different species, crop stages, cultural and water managements.
Keywords: evapotranspiration; biomass production; photosyntetically active radiation; surface resistance